2011
DOI: 10.1007/s10457-011-9437-9
|View full text |Cite
|
Sign up to set email alerts
|

Local knowledge helps select species for forest restoration in a tropical dry forest of central Veracruz, Mexico

Abstract: Species for restoration forestry on degraded lands in the tropics are often restricted to a few well-known exotic timber species. This selection frequently leads to failed projects, as local people expect trees to cover a number of uses, not only timber. We studied local knowledge of the usefulness, scarcity and importance for wildlife of native tree species in central Veracruz, Mexico, a region with mainly secondary vegetation and remnants of tropical dry forest. Data were obtained from several workshops, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 39 publications
0
43
0
9
Order By: Relevance
“…Little of the work specific to dry forests takes fuel as the main topic, and rarely is it quantitative (see Turc and Mazzucco 1998;Castillo et al 2005). However, it seems that in the Americas fuel is usually the most important resource derived from the forest, with heavy usage by the poor (de Albuquerque et al 2005;Lucena et al 2007;del Castillo et al 2011;Suárez et al 2012). Ramos et al (2008) found that in the Caatinga region of Brazil local people identified 67 plants as combustible energy sources, only 37 of which were actually used.…”
Section: Suggested Geographic Priorities Asia Latin Americamentioning
confidence: 99%
“…Little of the work specific to dry forests takes fuel as the main topic, and rarely is it quantitative (see Turc and Mazzucco 1998;Castillo et al 2005). However, it seems that in the Americas fuel is usually the most important resource derived from the forest, with heavy usage by the poor (de Albuquerque et al 2005;Lucena et al 2007;del Castillo et al 2011;Suárez et al 2012). Ramos et al (2008) found that in the Caatinga region of Brazil local people identified 67 plants as combustible energy sources, only 37 of which were actually used.…”
Section: Suggested Geographic Priorities Asia Latin Americamentioning
confidence: 99%
“…G. Nicholson (Bignoniaceae)--are characteristic of secondary vegetation and are prevalent in mature forests. They have a high cultural importance and are also essential for wild life, although they are scarce in the region at present (Suárez et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…G. Nicholson (Bignoniaceae); características de vegetación secundaria y notables en bosques maduros. Tienen alta importancia cultural y también son fundamentales para la vida silvestre, aunque, actualmente son escasas en la región (Suárez et al, 2012).…”
Section: Introductionunclassified
“…Cedrela odorata, have been promoted to landowners as easily seeded with well-known management techniques, there are many other local species that can provide numerous benefits to both communities and biodiversity conservation (Griscom et al 2005, Suarez et al 2012.…”
Section: The Central American Tropical Dry Forest and Tree Planting Imentioning
confidence: 99%
“…Tabebuia crysantha is also valued locally and listed as endangered but is not available in local nurseries, and several studies have compiled lists of species that demonstrate cultural and environmental utility (Williams-Linera and Lorea 2009, Griscom et al 2005, Suarez et al 2012). …”
Section: The Central American Tropical Dry Forest and Tree Planting Imentioning
confidence: 99%